2019
DOI: 10.1037/edu0000353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grade retention on students’ motivation: A longitudinal study over 3 years of secondary school.

Abstract: Despite the fact that grade retention is now seen as controversial in many quarters, it remains common practice in numerous countries. Previous research on the effects of grade retention on student development has, however, generated ambiguous results, particularly in terms of motivational outcomes. This ambiguity has been attributed in part to a lack of high-quality studies including a longitudinal design, a suitable comparison group, and adequate statistical control of preretention differences. Based on long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 66 publications
(105 reference statements)
7
57
0
2
Order By: Relevance
“…Our results reveal only an immediate negative effect in the year of grade retention decision on school satisfaction (but not on life satisfaction) that, however, vanishes quickly within the subsequent years after grade repetition. Unlike previous studies, which mainly used growth curves and propensity score matching [65,84], and similar to the longitudinal study on students' motivation by Kretschmann et al [58], we do not find any evidence for an enduring negative impact of grade repetition on students' well-being. From a longitudinal perspective, grade retention and repetition do not seem to be purposeless; our results indicate its effectiveness, starting already in the year of grade repetition.…”
Section: The Effect Of Grade Retention and Repetition On Students´welsupporting
confidence: 65%
See 1 more Smart Citation
“…Our results reveal only an immediate negative effect in the year of grade retention decision on school satisfaction (but not on life satisfaction) that, however, vanishes quickly within the subsequent years after grade repetition. Unlike previous studies, which mainly used growth curves and propensity score matching [65,84], and similar to the longitudinal study on students' motivation by Kretschmann et al [58], we do not find any evidence for an enduring negative impact of grade repetition on students' well-being. From a longitudinal perspective, grade retention and repetition do not seem to be purposeless; our results indicate its effectiveness, starting already in the year of grade repetition.…”
Section: The Effect Of Grade Retention and Repetition On Students´welsupporting
confidence: 65%
“…The consequence of a grade repetition has been, so far, considered primarily in relation to academic achievement in individual school subjects and student's motivation [58][59][60]. Meta-analyses based mostly on studies from 1990s found mixed evidence on the efficacy of early grade repetition showing it rather as an ineffective intervention for later academic achievement and socioemotional adjustment [61,62].…”
Section: The Effect Of Transitions On Students' Well-beingmentioning
confidence: 99%
“…Empirische Befunde -basierend auf amerikanischen Daten -zeigen den negativen kausalen Effekt des Wiederholens einer Schulklasse in der frühen Bildungsphase auf den Erwerb eines Schulabschlusses, sich an einer Universität einzuschreiben und ein Studium erfolgreich zu absolvieren (Andrew 2014). Eine aktuelle Studie für Deutschland belegt gleichermaßen kurzfristig negative Effekte einer Klassenwiederholung, die sich jedoch längerfristig wieder abschwächen können (Kretschmann et al 2019). Frühe negative Erfahrungen im Bildungssystem können demzufolge langfristige Folgen haben.…”
unclassified
“…This means that the reason that is usually given to explain any negative effects of grade repetition on school performance is not substantiated. After all, it is often assumed that the awareness of being retained has such a negative effect on the self-concept and the motivation of the student that school performance is more likely to suffer (Alexander, Entwistle, & Dauber, 2003;Kretschmann, Vock, Lüdtke, Jansen, & Gronostaj, 2019). However, on the basis of research into social comparison theories (Huguet et al, 2009) and the extensively studied and robust 'Big-Fish-Little-Pond-Effect' (BFLPE) (Marsh, 1987;Marsh et al, 2014), one may expect that a pupil who, by repeating a grade, performs better in comparison with the new class group will experience a more favorable self-concept and associated well-being (Marsh, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%